2018
DOI: 10.1097/aap.0000000000000742
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Spinal Myoclonus Complicating Lumbar Transforaminal Epidural Steroid Injection

Abstract: Segmental spinal myoclonus is a rare complication after lumbar transforaminal epidural steroid and local anesthetic injection. Pain physicians should be aware of this potential complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Although a LEI is generally considered a safe procedure, it is associated with several complications, such as hematomas, allergic reactions, and infections. 8,9 Infections after lumbar surgery have a considerable impact on recovery. The infection rate after posterior lumbar instrumented surgical procedures is approximately 3%.…”
Section: Introductionmentioning
confidence: 99%
“…Although a LEI is generally considered a safe procedure, it is associated with several complications, such as hematomas, allergic reactions, and infections. 8,9 Infections after lumbar surgery have a considerable impact on recovery. The infection rate after posterior lumbar instrumented surgical procedures is approximately 3%.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Although many studies have reported that there are several adverse reactions to the treatment of lumbar disc herniation by epidural injection of glucocorticoids, common complications include nausea, headache, dizziness, facial flushing, and vasovagal attack. [18] Some rare major complications reported include paralysis, cerebrospinal fluid leakage, spinal cord infarction, cerebral ischemia, spinal cord myoclonus, and epidural hematoma inhibition of the hypothalamic-pituitaryadrenocortical axis, [2,[18][19][20][21] and most of the adverse reactions can be attributed either to direct damage of blood vessels or the injection of drugs into the blood vessels. It is suggested that the exact location of the puncture needle, the use of nongranular glucocorticoids, such as betamethasone, real-time fluoroscopy, digital subtraction angiography, and the operator's familiarity with the contrast pattern of fluoroscopy should be used as much as possible to reduce the occurrence of these risks.…”
Section: Discussionmentioning
confidence: 99%
“…The physiologic characteristics of segmental myoclonus include burst duration ranges between 50 and 500 milliseconds without caudo-rostral propagation. 26,27 The physiologic characteristics of propriospinal myoclonus include long burst durations typically ranging from~150 to 450 milliseconds (can be even longer). Conduction velocity of the efferent volley ranges from 5 to 15 m/sec limited to the spinal cord without any cranial nerve innervated muscle activation.…”
Section: Brainstem Myoclonusmentioning
confidence: 99%